In Vitro Propagation of Temulawak (Curcuma xanthorrhiza Roxb.) - Samanhudi, Samanhudi; Yunus, Ahmad; Pujiasmanto, Bambang; Saras, Anindya (Jurnal Jamu Indonesia, 2017)
Problems encountered in the development of herbal medicine industry is that most of the raw materials (80%) came from the forest or natural habitats and the rest (20%) of the results of traditional cultivation. The research is focused to get the propagation techniques of temulawak by in vitro using various combinations of IBA and BAP concentration, each consisting of 0, 1, 2, 3, 4 ppm. The purpose of this research is to gain a plant propagation technique of temulawak through the use of IBA and BAP concentration so as to provide a quality seeds. The results showed that the highest shoots obtained at 1 ppm IBA and 3 ppm BAP treatment with a buds height of 15.9 cm. Treatment of 0 ppm IBA and 4 ppm BAP produces the highest buds number by 4 buds. While the highest number of leaves obtained in 2 ppm IBA and 3 ppm BAP treatment with total of 18 leafs. The highest length of leaf obtained in the treatment of 3 ppm IBA and 2 ppm BAP with a length of 14.6 cm. Variable highest number of roots was obtained at treatment of 4 ppm IBA and 1 ppm BAP with root number exceeds 30 pieces with very many hair roots and the highest root length was obtained at treatment of 2 ppm IBA and 0 ppm BAP with a length of 15.6 cm. Based on these results it can be concluded that the IBA and BAP treatment at various concentrations can affect the propagation and growth of temulawak explants.